(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This article is devoted to lightweight concrete with porous aggregates. Varieties of porous aggregates of organic and mineral origin are given. The technology for producing lightweight concrete is considered, the main physical and technological properties of such concrete and the scope of their application for lightweight concrete are given